Experimental Evaluation of the Shadowing of a Planar Antenna Caused by a Quadcopter Frame - Heydarov, Ibrahim; Brodnevs, Deniss (Electrical, Control and Communication Engineering, 2020)
The use of mobile data transfer can significantly increase the range of the remote-controlled operation of multirotor aerial vehicles. The planar antennas of ready-to-use 3G/LTE cellular communication dongles provide a low-cost and lightweight communication solution. In this paper, antenna shadowing caused by a quadcopter frame is experimentally investigated. The communication module is a 3G/LTE “Huawei 3372h” dongle with two planar built-in antennas and a receiver diversity function. The quadcopter frame is a widely used “F450” with Nylon arms and a PCB centre. It has been found that in order to minimize the antenna shadowing effect, planar antennas should be installed at the bottom of the frame, in parallel with the frame, with an air gap not less than the distance to the outer boundary of the reactive Near Field (NF).